Breeding success and its correlates in native versus invasive secondary cavity-nesting birds. (3rd July 2021) - Lermite, Françoise; Kark, Salit; Peneaux, Chloe; Griffin, Andrea S.
ABSTRACT: Australian cavity-nesting birds in urban habitats can encounter strong competition for nesting cavities. This results from the shortage of old large hollow-bearing trees in urban areas and because cities often host a suite of alien birds, including cavity-nesters. However, it is unclear whether some behavioural differences are involved with access to nesting cavities. We aimed to examine parental nest attendance, nest disturbance and breeding success in native parrots and the most common invasive urban bird in Australia, the Common Myna, Acridotheres tristis . We installed 78 experimental nest boxes in Newcastle, the second largest city in New South Wales, Australia, to compare native parrots and Mynas. We found that despite occupying nest boxes equally, native parrots had significantly lower breeding success, lost more clutches to hatch failure, exhibited lower levels of parental nest attendance, and encountered higher levels of nest disturbance than the alien Myna. These findings provide important insight into the breeding success of native and alien secondary cavity-nesting birds in cities. Evaluating the effectiveness of urban nest boxes will help guide future research and management aimed at optimising nest box design for maintaining native cavity breeders.